Postaci aniołów i diabłów w wybranych intermediach staropolskich - Mieszek, Małgorzata (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2005)
The article introduces various aspect of angelic and devilish presentation and shows some functions they were supposed to fulfil in old Polish interludes. There are almost no records about physical appearance of havenly messengers. They were usually presented as static characters, which after delivering their speech, according to staging clues, limited themselves to entrance or descent from the stage. As far as angels’ functions were concerned, they used to mediate between humans and God, from whom they passed vital messages. Moreover, individuals were usually forewarned of damnation and proved to be weak and unable to keep their promises (Chłop oskarża ojca Adama). Additionally, angels took care of human beings, which however, not always brought them satisfaction. That is why the Angels were “mątny” (‘cheerless’) in interludes Gryzidzban because of the failure in fight with the Devil. Occasionally, messengers form God revealed as periolous, when they deterred devilish tempters from winning over human soul. On the other hand, the stron faith in heavenly messengers made it possible to present some characters that posed as angels and their abuses. That is why, the fraud deceived gullible widower and deprived him o f his “precious” items (Wdowiec z Usarzem niebieskim). Not only did old Polish interludes describe functions and appearance of angels but also showed the place lhat heavenly messengers came from. Heaven existed as a dreamland in aulhors' imagination. It could have been described as the splendid palace (Maksym, Denis, Rycki, Wołowcowie) or prosperous farm, where untroubled people live eternally. Furthermore, some of the characters, living people, could visit the great beyonds, escorted by an angel. After such an unusual trip, they revealed what they had seen and sometimes changed their lives for better (like Jew did after visiting hell in the play Komunija duchowna świętych Borysa i Gleha). Such plot patterns used to be typical for visionary literature such as St. Peter's Apocalypse. In contrast to the virtues characters, the devils were presented in quite a different way. The evildoers have been presented in a more dynamic way. Interludes described them as usually balak individuals that would often use violence in their communication with people. Devils were able to change into any material form. Therefore, they could appear as a peasant, a cook, or a foreigner (e.g. German). Nevertheless, different faults of character and inconveniences they had to bother with brought devils closer to people. Demons could have been accused of being inconsiderate and indolent because of being poor at capturing new souls for the undergrounds (Diabeł z Tatarzynam i Śmiercią). Consequently, not only did they entertain people but also delude human beings easily. Besides, devils from old Polish interludes had a greater force of convincing haw dangerous and malicious it would be after taking an individual to hell. Descriptions of the place of damnation were supposed to frighten the audience and to make those who participated in the performance improve their lives. Devils presented different kinds of brutal corporal punishments and various ways of inflicting pain on sinners. Piercing, amputating limbs or burning and frying damned people - these are only a few from a wide range of devilish tortures. Hell as the opposite of heaven was located underground. The darkness that was said to cover this place could be seen as another kind of punishment. It is clearly seen that apart from entertaining qualities old Polish interludes played a moralistic role. Even though oversimplification could be inappropriate, one may venture to make a statement that the devils surpassed angels in terms of hilarious behaviour as well as vivid, still ironic and delusive, way of warning prospective sinners.